A fighter's record : issued in honor of F.W. Foerster commemorating his seventy-fifth birthday and his fifty year struggle against pan-Germanism. (New York : Society for the Prevention of World War 3, 1944)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Foerster, Frederick Wilhelm; Wereldoorlog 2